The effect of teaching experience and training on teachers’ performance of state senior high schools - Zulkarnain, Zulkarnain; Fitria, Happy; Puspita, Yenny (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study aimed to determine: (1) the effect of teaching experience on teachers’ performance; 2) the an effect of training on teachers’ performance; and (3) the effect of training on teachers’ performance. The data in this study were collected through distributing questionnaires to respondents. The results of filling out the questionnaire were analyzed by using multiple regression analysis through the t test, F test, and determination coefficient test. The population in this study was 703 State Senior High School teachers in Ogan Komering Ulu Selatan Regency. The sample in the study was taken by using purposive sampling technique; thus, the sample of this study were 160 teachers. The results of the study found that: (1) there was an effect of teaching experience on the performance of teachers; 2) There was an effect of training on the performance of the teachers; 3) There was an effect of teaching experience and training simultaneously on the performance of teachers.